1992
DOI: 10.1056/nejm199209033271005
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Seizures after Treatment for Cerebral Cysticercosis

Abstract: After medical treatment of neurocysticercosis, there is usually remission or marked improvement in the associated seizure disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(67 citation statements)
references
References 28 publications
2
64
0
1
Order By: Relevance
“…Indeed, seizure s may be a late manifestation of neuro c y s t i c e rcosis e v e n after adequate treatment, because cicatricial tissue remains as a permanent sequela 25,26 . Two retrospective studies published in 1992 found striking diff erences in the evolution of seizures in favor of antiparasitic treatment 6,27 , but in 1995 a controlled trial showed no diff e rences among patients treated with albendazole, praziquantel or cort i c o s t e roids alone 2 8 . In Brazil, however, the majority of patients diagnosed as having round intracranial calcifications on CT-s c a n images and epilepsy had never been submitted to therapy with praziquantel or albendazol 2 , 9 , 2 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, seizure s may be a late manifestation of neuro c y s t i c e rcosis e v e n after adequate treatment, because cicatricial tissue remains as a permanent sequela 25,26 . Two retrospective studies published in 1992 found striking diff erences in the evolution of seizures in favor of antiparasitic treatment 6,27 , but in 1995 a controlled trial showed no diff e rences among patients treated with albendazole, praziquantel or cort i c o s t e roids alone 2 8 . In Brazil, however, the majority of patients diagnosed as having round intracranial calcifications on CT-s c a n images and epilepsy had never been submitted to therapy with praziquantel or albendazol 2 , 9 , 2 9 .…”
Section: Resultsmentioning
confidence: 99%
“…In countries where it is endemic, neurocysticercosis may affect 2-4% of the population. 1 In many Latin American countries, such as Ecuador, it is the major cause of late-onset epilepsy, accounting for more than 50% of such cases. 2 However, neurocysticercosis is not just found in remote areas or developing countries.…”
mentioning
confidence: 99%
“…1 With cysticidal treatment, the natural history of the infection is accelerated. 2 A successfully treated lesion rapidly progresses from an inert cyst with a live scolex to involution and calcification. During the process of cyst death the host mounts an inflammatory response to released larval proteins, accompanied by a cellular infiltrate and edema.…”
Section: Introductionmentioning
confidence: 99%
“…Although seizures may persist after treatment, patients with calcified lesions are assumed to be cured of active disease. 2 We report a case of neurocysticercosis in which a patient who was assumed to be cured of active infection presented with sudden onset of headache, associated with inflammation and edema around lesions previously shown to be calcified. …”
mentioning
confidence: 99%